Glycemic control after initiating direct-acting antiviral agents in patients with hepatitis C virus and type 2 diabetes mellitus using the united states integrated healthcare system - Alicia Halim Wong; John Sie; Angela Chen; Basuki Gunawan; Joanie Chung; Nazia Rashid (Wolters Kluwer Medknow Publications, 2020)
Objective: Hepatitis C virus (HCV) has an increased risk of Type 2 diabetes mellitus (T2DM). Prior studies found that the eradication of HCV with direct-acting antiviral (DAA) agents led to improved glycemic control in patients with T2DM. We aimed to identify the association between HCV eradication and glycemic control in patients diagnosed with HCV and T2DM. Methods: A retrospective observational study was conducted to identify adult patients diagnosed with HCV from January 1, 2014, to August 31, 2017. Patients were included if they were initiated on one of the following DAA agents within the study period: Sofosbuvir/velpatasvir, sofosbuvir/ledispavir, elbasvir/grazopevir. Patients were also required to have the diagnosis of T2DM. The primary outcome of this study was the average change in glycosylated hemoglobin (HbA1c) pre- versus post-DAA agents. Findings: Our final cohort consisted of 996 patients diagnosed with HCV and T2DM: Patients who achieved sustained virologic response (SVR) (n = 937, 94%) and those who did not achieve SVR (n = 59, 6%). In the SVR group, there was a 0.3950% reduction in HbA1c (P < 0.0001) and in those who did not achieve SVR group, there was 0.3532% reduction in HbA1c (P = 0.0051). In the overall study population, SVR group had 0.04% more reduction in HbA1c but was not statistically significant (P = 0.7441). Conclusion: Both groups had statistically significant reductions in HbA1c when comparing the mean change in average HbA1c pre-versus post-DAA agent. Patients who achieved SVR had a greater absolute reduction in HbA1c by 0.04%; however, this was not statistically significant.